2020
DOI: 10.3390/cancers12082052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative and Pro-Apoptotic Effects of Short-Term Inhibition of Telomerase In Vivo and in Human Malignant B Cells Xenografted in Zebrafish

Abstract: Besides its canonical role in stabilizing telomeres, telomerase reverse transcriptase (TERT) may promote tumor growth/progression through extra-telomeric functions. Our previous in vitro studies demonstrated that short-term TERT inhibition by BIBR1532 (BIBR), an inhibitor of TERT catalytic activity, negatively impacts cell proliferation and viability via telomeres’ length-independent mechanism. Here we evaluate the anti-proliferative and pro-apoptotic effects of short-term telomerase inhibition in vivo in wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The mechanism(s) by which high TERT expression ultimately facilitates cancer progression and constitutes a prognostic factor are not completely elucidated, and seems not be attributable only to TERT's ability to maintain telomere length. Indeed, accumulating evidence suggests that TERT may also contribute to carcinogenesis via telomere lengthindependent mechanisms, including enhancement of proliferation, resistance to apoptosis, inflammation, invasion and metastasis altogether contributing towards a more aggressive phenotype of cancer cells (10,11,(42)(43)(44)(45)(46)(47)(48)(49)(50). Therefore, it is conceivable that the -124 C>T TERT promoter mutation, inducing higher expression of TERT in the tumour, results in the increased severity of disease as we observed in our cohort of OCSCC patients.…”
Section: Discussionmentioning
confidence: 51%
“…The mechanism(s) by which high TERT expression ultimately facilitates cancer progression and constitutes a prognostic factor are not completely elucidated, and seems not be attributable only to TERT's ability to maintain telomere length. Indeed, accumulating evidence suggests that TERT may also contribute to carcinogenesis via telomere lengthindependent mechanisms, including enhancement of proliferation, resistance to apoptosis, inflammation, invasion and metastasis altogether contributing towards a more aggressive phenotype of cancer cells (10,11,(42)(43)(44)(45)(46)(47)(48)(49)(50). Therefore, it is conceivable that the -124 C>T TERT promoter mutation, inducing higher expression of TERT in the tumour, results in the increased severity of disease as we observed in our cohort of OCSCC patients.…”
Section: Discussionmentioning
confidence: 51%
“…Nonetheless, as demonstrated previously [24], we found that circulating TERT levels at T2 and ∆TERT levels were predictive of tumor response and prognostic of disease outcome. This is not surprising in light of accumulating evidence suggesting that, besides its canonical role in stabilizing telomeres, TERT may promote tumorigenesis through extra-telomeric functions, including enhancement of proliferation, resistance to apoptosis, inflammation, invasion and metastasis altogether contributing towards the higher resistance of cancer cells [36][37][38]. Therefore, endowed with these non-telomeric functions, TERT can participate in all the major characteristics of the cancer phenotype, thereby supporting its role as a potential prognostic tumor marker.…”
Section: Discussionmentioning
confidence: 93%
“…Shammas and co-workers reported that siRNA-mediated inhibition of telomerase activated both mitochondrial- and death-receptor-mediated pathways in Barrett’s adenocarcinoma SEG-1 cells [ 44 ]. In addition, Giunco et al observed that short-term inhibition of TERT by BIBR1532 in human malignant B cells xenografted in zebrafish led to apoptosis with induction of DDR [ 45 ].…”
Section: Discussionmentioning
confidence: 99%